Analysis of Water Pollution Using Different Physicochemical Parameters: A Study of Yamuna River - Sharma, Rohit; Kumar, Raghvendra; Satapathy, Suresh Chandra; Al-Ansari, Nadhir; Singh, Krishna Kant; Mahapatra, Rajendra Prasad; Agarwal, Anuj Kumar; Le, Hiep Van; Pham, Binh Thai (Frontiers in Environmental Science, 2020)
The Yamuna has become one of the most polluted rivers in India as well as in the world because of the high-density population growth and speedy industrialization. The Yamuna is mainly polluted in the downstream of New Delhi, which dumps a large portion of its waste into the river but now its water quality is also degraded year by year at Dehradun. River Yamuna plays a very crucial role in Dehradun’s geography. River Yamuna is severely polluted and needs urgent revival. Uttarakhand has always been a tourist spot and experiences heavy tourists perennially and Dehradun being the capital city also bears the brunt. River Yamuna is polluted in Dehradun due to exceptional tourist activity, poor sewage facilities, and insufficient wastewater management amenities. A lot of actions and measures have been taken by the government so that pollution can be reduced but often fail because of the unsupportive population. The measurement of the quality can be done by water quality assessment. In this study, the water quality index was calculated for river Yamuna using monthly measurements of twelve physicochemical parameters at Dehradun. Trend analysis for river water pollution has been performed using different parameters for the years 2019 to 2023 at Dehradun. The study shows that the values of four parameters named Temperature, Total Coliform, TDS, and Hardness are increasing yearly; whereas the values of pH and DO are not rising heavily. The considered Physico-chemical parameters for the study are TDS, Chlorides, Alkalinity, DO, Temperature, COD, BOD, pH, Magnesium, Hardness, Total Coliform, and Calcium. The values of the considered physicochemical parameters have been monitored using various monitoring stations installed by the Central Pollution Control Board (CPCB), India.